Ministry Of Health Gezira State Gezira Malaria Free Initiative 2004 -2005 - Sulaiman, Abbas (Gezira Journal of Health Sciences, 2004)
Situation Analysis and Objectives . Gezira State is one of the largest States in Sudan with an area of 35.304 km 2 and population 3.6692000. it is administratively divided into seven localities with malaria units in each locality. Malaria is a major health problem in the State. Plasmodium falciparum is the predominate species (> 95 %) and anopheles arabiensis is the sole vector. More than 31 % of out patient visitors are malaria and about 35.6 % of the admission in the State health facilities are due to malaria and about 20.1 % of the total deaths for the year (2002). The main strategic directions are early diagnosis and prompt treatment. Selective vector control measures including insecticides, treated nets, early forecasting and appropriate respond to epidemics, developing partnership and applied field research. Control measures in Gezira State is affected by irrigation scheme favourable breeding sites, broken pipes, poor drainage system, insecticide resistance and poor financial support, insufficient epidemiological and health information system and more over poor diagnostic facilities in both public and private sector.